Interrogative Listening Ability of Students Of The 2024/2025 Class of Indonesian Language And Literature Education Study Program FKIP Bung Hatta University - Gusnetti, Gusnetti; Naini, Ineng (Universitas Negeri Padang, 2025)
This study aims to describe the listening ability of students of the 2024/2025 batch in interviewing resource persons. This study uses a qualitative descriptive research design. The subject in this study is a student of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Hatta University, Class of 2024/2025, with the object of the research being one resource person who is considered capable of providing the information needed by the interviewer. In listening skills. The research design used is a qualitative descriptive design. Data were collected by interview methods and descriptive analysis, using recordings. The data collection process was carried out by interviewing resource persons with a duration of 10-15 minutes. The results of the interviews were written by each person based on their understanding of the information conveyed by the speakers. Data analysis is carried out after the data is collected based on qualitative descriptive research. Data was collected in 3 groups, including the education sector, social media and learning media. Each group prepared 5 questions. The results of the study showed that the ability of students to open the interview was good, asking the question material was very good, and closing the interview was also good. The ability of students to write interview results with a very good category of 4 people (33.33), a good category of 5 people (41.67) and a medium category of 3 people (25%). Thus, it can be concluded that the ability to listen to the interrogation of students for the 2024/2025 Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Hatta University is good.